Cherry Fruit Fly, Rhagoletis cingulata (Loew) (Insecta: Diptera: Tephritidae) - Howard V. Weems, Jr. (EDIS)
Revised! EENY-203, a 3-page illustrated fact sheet by H.V. Weems, Jr., is part of the Featured Creatures collection. It describes this species of fruit fly that attacks cherries and causes wormy fruits — synonyms, distribution, identification, life history and habits, and hosts. Includes references. Published by the UF Department of Entomology and Nematology, August 2009.